Studies of Novel Sulfapyridine Derivatives Containing Schiff Bases and Co(II), Ni(II) and Zn(II) Complexes: Synthesis, Experimental and Theoretical (DFT) Approach for Characterization and Biological Efficacy - Sahal, Hakan; Fellah, Mehmet Ferdi; Gur, Seher; Kaya, Mehmet; Turkoglu, Semra; Canpolat, Erdal (Chem Soc Pakistan, 2017)
Two new ligands were synthesized from sulfapyridine with 5-bromosalicylaldehyde (for (LH)-H-1) and 5-nitrosalicylaldehyde (for (LH)-H-2). Mononuclear complexes with metal ligand ratio 1:1 were prepared with Co(II), Ni(II) and Zn(II) salts. Their structures were elucidated on the basis of elemental analyses, IR, H-1-NMR and C-13-NMR spectra, electronic spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA). The synthesized compounds were tested for antimicrobial activity against bacterial and fungi in vitro by the minimum inhibitory concentration (MIC) method. All of the selected compounds showed strong antimicrobial activities against test microorganisms (32-256 mu g/mL). Furthermore, the antioxidant activities of the ligands and their complexes were determined by DPPH, metal chelating activity methods in vitro. The obtained IC50 value of the DPPH activity for the L-1-Ni complex (1.155 perpendicular to 0.054 mu M) and that of the metal chelating activity for the (LH)-H-2 ligand (% = 75 +/- 5.624) were higher than the values obtained for the other compounds. The computed stretching frequencies, UV spectral data and NMR spectra values were found to be in good agreement with experimental data.
Keywords: Antimicrobial activity; DPPH; Metal Chelating Activity; Sulfa drugs; DFT; Coordination compounds